Rancan Bangun Sistem Informasi Penjadwalan Mata Pelajaran Berbasis Web - Manase Sahat H Simarangkir (LPPM Poltek ST Paul, 2021)
Scheduling subjects is very important in the course of teaching and learning activities in schools, this schedule aims to support, expedite, and increase discipline in the process of teaching and learning activities. Several problems often occur related to the scheduling management of subjects at SMK Puja Bangsa, because it is still done manually. The curriculum section processes scheduling data using the ms.excel application then prints the schedule, so that the course schedule creation process is ineffective because the process tends to take a long time and the resulting schedule information is less accurate. This research is a software development research that aims to design a Web-Based Subject Scheduling Information System. This system is designed to make it easier to manage the schedule of subjects in school. This software development uses the waterfall development model. The system was built using the PHP programming language with the Codeigniter and MySQL framework for storing databases. The method used in this research includes data collection, literature study related to scheduling web-based subjects. Observations and interviews are used to determine user responses to the information system that has been designed. The results obtained from the design of this system is a subject scheduling information system that can facilitate the scheduling process so that the learning process can be more effective and efficient.